(untitled) (LEGAL DIALOGICA, 2025)
This study examines the legal analysis of village community empowerment in the community empowerment, village, and protection of girls’ services in Sidenreng Rappang Regency (case study at the Sungguminasa District Court, Class IA). This writing uses an empirical research type, namely a research procedure used to examine human life, history, behavior, and kinship relationships. With the form of written words, speech, or interviews and people and behavior that can be observed. The results of the study indicate that the implementation of village community empowerment in the village law, namely the aspirations and participation of the community in empowerment programs, is a form of participation and commitment as a group to build the village. The success of the implementation of the Village Law in empowering village communities depends heavily on good implementation in the field. The government, the community, and all related parties need to synergize to ensure that this law can be implemented effectively and provide real benefits for village communities.. Obstacles encountered in the process of empowering rural communities and villages in Sidrap Regency include internal and external obstacles. Internal obstacles include a lack of human resources, knowledge, and skills, as well as low community participation and awareness. External obstacles include limited access to education, infrastructure, technology, and information, as well as a lack of coordination between stakeholders and support from related parties. Recommendations for writing: Parties involved in village community empowerment programs should focus more on village empowerment programs in accordance with the mandate of laws and regulations; (2) Village communities and non-governmental organizations should participate in channeling aspirations related to village community empowerment. Abstrak: Penelitian ini mengkaji tentang analisis hukum terhadap pemberdayaan masyarakat desa di dinas pemberdayaan masyarakat, desa, dan perlindungan anak perempuan di kabupaten sidenreng rappang(studi kasus di pengadilan negeri sungguminasa kelas IA). Penulisan ini menggunakan tipe penelitian empiris, yakni prosedur penelitian yang digunakan untuk meneliti kehidupan manusia, sejarah, tingkah laku, dan hubungan kekerabatan. Dengan bentuk kata-kata yang tertulis, ucapan, atau wawancara dan orang-orang serta perilaku yang mampu untuk diamati. Hasil penelitian menunjukkan bahwa Penerapan pemberdayaan masyarakat desa dalam undang-undang desa yaitu aspirasi dan keikutsertaan masyarakat dalam program pemberdayaan merupakan bentuk partisipasi dan komitmen sebagai sebuah kelompok untuk membangun desa. Keberhasilan penerapan UU desa dalam pemberdayaan masyarakat desa sangat bergantung pada implementasi yang baik di lapangan. Pemerintah, masyarakat, dan semua pihak terkait perlu bersinergi untuk memastikan bahwa undang-undang ini dapat diimplementasikan secara efektif dan memberikan manfaat yang nyata bagi masyarakat desa, Hambatan yang dihadapi dalam proses pemberdayaan masyarakat desa dan desa di Kabupaten Sidrap yaitu Hambatan Internal dan Hambatan Eksternal, hambatan internal meliputi kurangnya sumber daya manusia, pengetahuan, dan keterampilan, serta rendahnya partisipasi dan kesadaran masyarakat. Sedangkan hambatan eksternal mencakup terbatasnya akses terhadap pendidikan, infrastruktur, teknologi, dan informasi serta kurangnya koordinasi yang antar pemangku kepentingan dan kurangnya dukungan dari pihak terkait. Rekomendasi penulisan : Bagi pihak terkait program pemberdayaan masyarakat desa agar lebih fokus terhadap program pemberdayaan desa sesuai amanah peraturan perundang-undangan; (2) Bagi pihak masyarakat desa serta lembaga non pemerintahan agar turut serta berpartisipasi dalam menyalurkan aspirasi terkait pemberdayaan masyarakat desa.